ANALISIS KUALITAS LAYANAN FRONTLINER TERHDAP PERTUMBUHAN DANA PIHAK KETIGA STUDI PADA PT BANK SYARIAH MANDIRI CABANG BEKASI PONDOK GEDE - Haryo Gumilang; Purnama Putra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The main activity of the bank is the provision of services. Banks as financial institutions engaged in services, must be able to provide the best service (Service Excellence) in order to win competition in increasingly competitive situations. Frontliners are officers who are in front of the banking hall that face directly to customers. This study aims to analyze how much influence the quality of service Frontliner (Customer Service, Teller, Security) on the growth of third party funds. In this study using primary and secondary data obtained from the official website of Bank Syariah Mandiri and questionnaires distributed to respondents. The method used is a quantitative method. The results of this study show partially that the quality of frontline service (Customer Service, Teller, Security) has a positive effect on third party funds. While simultaneously the quality of Customer Service services, Teller service quality, security service quality has a significant positive effect on the growth of third party funds. Future research is expected to expand the scope of research or compare variables and other factors.